Impact of green packaging solutions on consumer's buying behavior - Sadam Yaya (UCU, 2024)
In this study, the objective was to investigate the influence of green packaging solutions on consumer buying behavior in Uganda, with a specific focus on Riley Uganda Limited, a local firm. The research utilized a mixed-methods approach, incorporating quantitative questionnaires and qualitative interviews to examine the impact of various eco-friendly packaging materials onbrandloyalty, consumerpreferences, andpurchasingfrequency.Atotal of 67 employees participated in the study, yielding a favorable 76.1% response rate. The findings revealed that consumers increasingly associate brands using eco-friendly packaging with trustworthiness, leading to enhanced brand loyalty. Furthermore, the research discovered a significant correlation between consumer attitudes toward sustainability and their purchasing frequency. Additionally, participants expressed a willingness to pay a premium for products packaged sustainably. These insights highlight the necessity of marketing strategies that prioritize green packaging to align with evolving consumer values, thereby promoting responsible consumption and corporate social responsibility.